Oyster Mushroom Production Capacity Development, Diversification, and Marketing Strategy Management Processed Oyster Mushroom Products - Hasanah, Yaya; Nursa'adah, Nursa'adah; Febriyani, Dian; Hamzah, Tengku Mika Hakinen; Febrio, Hanif (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Rumah Jamur Sadam is one of the oyster mushroom producers in Medan Marelan that produces 7-12 kg/day with a capacity of 7,000 baglogs. The oyster mushroom production results are only marketed conventionally. Currently, partners can produce oyster mushroom seeds independently, but increased oyster mushroom production capacity has yet to be supported by increasing partner independence in baglog sterilization. The oyster mushrooms produced need to be diversified, and the marketing strategy for their processed products needs to be improved so that their market as Medan Marelan's leading product can be even more expansive. Based on the results of the analysis and observation, the problems faced by partners include a lack of equipment to support increasing oyster mushroom production capacity, diversification of oyster mushroom processed products that are still lacking in variety, the need for an online product marketing strategy to expand the market for oyster mushroom processed products as Medan Marelan's leading product. The solutions to these problems are introducing technology transfer goods, increasing the diversification of oyster mushroom processed products, and educating oyster mushroom processed product marketing strategies online to expand their market.